(3GdLhgQ GdfajS jTQM efXheI GdQFjSs - (3ehSi Hf EHQGgje Hf ehSi Hf eMeO , GdeJWHH GdHZOGOjs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdSWhQ GdKdGKI GdChdi ZjQ hGVMI (B:- (3GdEfSGf gh CTQa GdMjhGf dbhdg JYGdi(B" (3hdbO cQefG Hfi COe hLYdfGg(B" (3ddYHGOI s
(3BNQgG (B:s
(3bGd GHf NdcGf cGfJ EUGHJg YLjHI MSf GdYHGOI hdcfg cGf cKjQ GdefGbTI Je GdTQM s
(3GdfSNI HgG MhGTs
(3Yf fSNI (B- (3GdeDdas
(3fSNI KGfjI ai eLdOjfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdWHs